The Investment Conflict between British and Japan in the Federation of Malaya After the Second World War, 1946-1956 - Iqbal, Uqbah; Hussin, Nordin; Seman, Ahmad Ali (ASPENSI in Bandung, Indonesia, 2016)
ABSTRACT: The focus of this study is to unravel the conflict between British and Japanese investments in the Federation of Malaya from 1946 to 1956, after the Second World War. The method used in this study is based on the method of observation of the resources available in Libraries and the National Archives of Malaysia. After Japans defeat in the Second World War, on 15 August 1945, between the months of September 1945 until 1 April 1946, the British administration of Malaya back through the BMA (British Military Administration) with all Japanese assets in Malaya was placed under the British Custodian of Enemy Property. Meanwhile, the priority of the United States of America policy after the Second World War was to stop the spread of Communism during the Cold War. The United States of America saw Southeast Asia as a natural market for Japanese goods and a source of raw materials for the Japanese industry, also as an alternative to relations with the Chinese Communist government. The Federation of Malayaâs iron ore mining is considered important to the United States of America effort in connecting Japan and Southeast Asia. Although it led to friction with the British, but their main interest is to overcome the Communist threat in the region, especially from China. Japan did not indicate significant interest on the question of retrieving the whole importance of their economies to the extent as it did before the war, there was only an effort to recover their position in the Federation of Malayaâs iron ore mining.KEY WORDS: United States of America, British, economics interests, Japan, and Federation of Malaya government.Â Â About the Authors: Dr. Uqbah Iqbal is a Research Scholar and Alumnus of School ofÂ History,Â Politics and Strategy, Faculty of Social Sciences and Humanities UKM (National University of Malaysia), UKM Campus, 43650 Bangi, Selangor Darul Ehsan, Malaysia. Prof. Dr. Nordin Hussin and Dr. Ahmad Ali Seman are the Senior Lecturers at the School ofÂ History,Â Politics and Strategy, Faculty of Social Sciences and Humanities UKM, 43650 Bangi, Selangor Darul Ehsan, Malaysia. Corresponding authors are: uqbah@siswa.ukm.edu.my, nordin@ukm.my, and aasw@ukm.myHow to cite this article? Iqbal, Uqbah, Nordin Hussin & Ahmad Ali Seman. (2016). âThe Investment Conflict between British and Japan in the Federation of Malaya After the Second World War, 1946-1956â in TAWARIKH: International Journal for Historical Studies, Vol.7(2) April, pp.239-254. Bandung, Indonesia: Minda Masagi Press and UIN SGD Bandung, ISSN 2085-0980. Chronicle of the article: Accepted (November 27, 2015); Revised (January 25, 2016); and Published (April 28, 2016).